Pemantauan Kepadatan Lalu Lintas di Kota Banda Aceh Secara Non-Invasif Menggunakan Bluetooth Low Energy - Muhammad Ichsan; Dalila Husna Yunardi; Maya Fitria; Kurnia Saputra; Diky Wahyudi; Yahdina Ahsya; Rahmad Dawood (Prosiding SISFOTEK, 2025)
The rapid population growth in Banda Aceh City, reaching 259,538 inhabitants in 2024, has significantly increased traffic congestion and posed critical infrastructure challenges. Traditional video-based traffic monitoring systems raise privacy concerns due to the collection of personal data such as license plates and facial images. This research proposes a non-invasive traffic density monitoring system utilizing Bluetooth Low Energy (BLE) technology as a privacy-preserving alternative. The system architecture consists of three main layers: an Android-based mobile gateway for BLE signal detection, a cloud backend infrastructure using AWS services (API Gateway, Lambda, DynamoDB, and EventBridge) for data processing, and a web application developed with Next.js for visualization. Field testing conducted at Mesjid Raya Baiturrahman Bus Stop demonstrated that the system operates stably and effectively. The mobile gateway successfully detected BLE devices continuously, transmitted data to the backend without packet loss, and the web dashboard displayed traffic information through interactive maps and tables. The results indicate that BLE-based traffic monitoring provides an effective, and privacy-preserving solution for urban traffic management, particularly suitable for developing regions with limited technical infrastructure.